Risk - Lupton, Deborah 1963- (Routledge, 1999)
The author examines why risk has come to such prominence, she traces how risk has been constructed and introduces the main theories surrounding the subject. The book includes examples of the ways in which risk is experienced in everyday life.
Keywords: Perception du risque - Aspect social; Risico's; Risque - Aspect sociologique; Sociale aspecten; Gesellschaft; Risk perception -- Social aspects; Risk -- Sociological aspects; Soziologie; Soziologische Theorie; Risiko